1999
DOI: 10.1097/00004872-199917110-00017
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of enalapril 20 mg once daily versus 10 mg twice daily in terms of blood pressure lowering and patient compliance

Abstract: Enalapril 20 mg should be prescribed as 10 mg twice daily and measures taken to improve patient compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…However, 2 studies evaluating dosing frequency only compared once vs twice a day, finding a difference in adherence but not in clinical effects. 20,28 A study evaluating a wider range of dosing schedules failed to meet our inclusion criteria. 58 One study 22 comparing 2 vs 4 times per day dosing showed an improvement in medication adherence and in treatment outcome in the twice per day group.…”
Section: Commentmentioning
confidence: 99%
“…However, 2 studies evaluating dosing frequency only compared once vs twice a day, finding a difference in adherence but not in clinical effects. 20,28 A study evaluating a wider range of dosing schedules failed to meet our inclusion criteria. 58 One study 22 comparing 2 vs 4 times per day dosing showed an improvement in medication adherence and in treatment outcome in the twice per day group.…”
Section: Commentmentioning
confidence: 99%
“…For instance, a different intervention approach would be warranted if participants tended to miss medications repeatedly for the same reason than if they missed medications for different reasons across time. Many previously tested interventions to improve antihypertensive medication adherence took a one-size-fits-all approach, such as blister packs,8,9 reminders,10 copayment reduction,11 education and/or psychological intervention,2,12 self-monitoring,13 or regimen simplification 14. Even multifactorial interventions comprised a limited menu of intervention strategies that were provided to all participants 15.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple diseases and complex medicine regimes in elderly patients may compromise adherence even further [3,4]. Studies of regimen simplification, like reduced dose frequency, often focus on patient adherence only and fail to include measures of satisfaction or acceptability by patients or show that simplification leads to clinical improvements [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%